LncRNA ID2-AS1 suppresses tumor metastasis by activating the HDAC8/ID2 pathway in hepatocellular carcinoma. (28th January 2020) - Zhou, Yuqiang; Huan, Lin; Wu, Yangjun; Bao, Chunyang; Chen, Bing; Wang, Lu; Huang, Shenglin; Liang, Linhui; He, Xianghuo
Abstract: Metastasis is a core hallmark of cancer that leads to high mortality of cancer patients, especially in hepatocellular carcinoma (HCC). However, the underlying mechanisms of long noncoding RNAs (lncRNAs) in HCC metastasis remain largely unknown. We found that ID2-AS1 expression decreased in metastatic HCC cell lines and HCC tissues, and lower ID2-AS1 expression predicted reduced overall survival in HCC patients. ID2-AS1 significantly suppressed the migration, invasion and metastasis of HCC cells in vitro and in vivo . Mechanistically, ID2-AS1 regulated the transcription of its adjacent gene inhibitor of DNA binding 2 (ID2) by blocking the binding of histone deacetylase 8 (HDAC8) on the ID2 enhancer. Furthermore, ID2-AS1 and ID2 suppressed the Twist-induced epithelial-mesenchymal transition (EMT) in HCC cells. In addition, ID2 expression was also significantly decreased in HCC tissues and was positively correlated with ID2-AS1 in HCC tissues and HCC cell lines. Taken together, our findings demonstrated that ID2-AS1 regulated adjacent ID2 transcription by manipulating chromatin modification and that the newly identified ID2-AS1/ID2 axis suppressed HCC metastasis by regulating EMT processes. Our findings provide insights into the molecular mechanisms underlying the metastasis of HCC cells. Highlights: ID2-AS1 is significantly downregulated in hepatocellular carcinoma, and negatively associated with poor overall survival. ID2-AS1 interacts with HDAC8 and blocks the binding of HDAC8 to the ID2 enhancer, leading to a decrease in ID2 expression. ID2 expression is positively correlated with ID2-AS1 in HCC samples and HCC cell lines. The newly identified ID2-AS1/ID2 axis suppresses HCC metastasis by regulating EMT processes.